Fetomaternal Outcome of Pregnancy with COVID-19: An Observational Study in a Tertiary Care Hospital of Pakistan - Zareena Begum, Farhadia Sadaf, Haider Shah, Seema Amin, Maryam Afridi, Rukhsana Qureshi, Sania Tanveer Khattak, Naeem Awan (Pakistan Journal of Medical & Health Sciences, 2022)
Background: In December 2019, the new corona virus initially appeared in Wuhan, China, and has since spread to other nations around the world. On January 30, 2020, the World Health Organization believes that the new CoV-19 outbreak will be declared a public health emergency of international concern (PHEIC) by the World Health Organization. The mortality rate of this viral infection varies widely around the world, from 2% in Pakistan to 14.4% in Italy. In the early stages of the disease, lympopenia, raised transminase, proteinuria, increased LDH, and C-reactive protein levels are all common laboratory results. Patients treated with Covid have had severe pneumonia, ARDS, heart defects, sepsis and septic shock, and respiratory tract super infection, among other problems. Methodology: The Gynecology unit of the Saidu Group of Teaching Hospitals conducted this retrospective observational research study. Biochemical and radiological parameters of medical history, test findings, symptoms, pregnancy, and neonatal outcomes were noted in a pre-constructed data collection form. The study excluded patients who was treated in an outpatient setting. Results: There were a total of 121 patients, with a mean age of 27 and a standard deviation of 5, with a range of 19-40 years. Pregnant women reported their first pregnancy in 48.3% of cases (primigravida). 51.3 percent of SARS-Cov-2 patients were in their third trimester, whereas 34.7 percent were between 35 and 40 weeks of pregnancy. Pregnancy-induced hypertension (PIH) (16 instances), hypothyroidism (14 cases), and gestational diabetes (GDM) (9 cases) are the most common problems. More than half of the patients (53%) are asymptomatic. Cough (22 percent) and fever (11 percent) are the most common symptoms (11 percent ). As seen in table 1, the incidence of multiple organ failure was 2%. Lympopenia was a prevalent ailment (84 percent ). Bilateral invasion was discovered in a CT scan of 24 subjects. Conclusion: According to our findings, COVID-19 has a deleterious impact on the foetus. Although pregnant women do not appear to be more susceptible to COVID-19 complications than non-pregnant adults, previous research has suggested that pregnant women may be more at risk for negative pregnancy outcomes such as preterm birth, foetal pain and respiration, symptoms, and LBW in a newborn baby.